Platelet indices and the risk of pulmonary arterial hypertension: a two-sample and multivariable Mendelian randomization study - Li, Yinuo; Liu, Xi; Hong, Qian; Xu, Rui (Frontiers in Cardiovascular Medicine, 2024)
Background: Recent epidemiological studies have indicated a correlation between platelet indices and pulmonary arterial hypertension, yet the causality between them remains unclear. To explore the causal relationship between four platelet indices and pulmonary arterial hypertension, with the aim of providing a theoretical basis for clinical prevention and treatment.Methods: Single-nucleotide polymorphisms (SNPs) associated with platelet-related traits were selected as exposure factors from published genome-wide association studies (GWAS), including: platelet count (PLT), plateletcrit (PCT), mean platelet volume (MPV), and platelet distribution width (PDW). Summary-level data for pulmonary arterial hypertension (PAH) were obtained from the FinnGen study (248 cases and 289,117 controls). Two-sample and multivariable Mendelian randomization analyses were conducted to assess the causal relationship between exposure factors and the risk of outcomes. The inverse variance weighted (IVW) method was utilized as the primary MR analysis approach, supplemented by weighted median, mode-based estimation, MR-Egger regression, and the MR Pleiotropy Residual Sum and Outlier (MR-PRESSO) test to detect and adjust for pleiotropy, ensuring the reliability of the results through sensitivity analysis.Results: (1) The IVW results from the two-sample MR analysis showed a positive causal association between platelet count and the risk of developing PAH ((OR = 1.649, 95%CI: 1.206-2.256, P = 0.0017), with the sensitivity analysis confirming the robustness of the causal relationship. The MR-Egger intercept analysis did not detect potential pleiotropy (P = 0.879). (2) The MVMR results showed no statistically significant causal relationship between these four markers and the risk of developing PAH. After adjusting for collinearity, a direct positive causal association was observed between platelet count and the risk of developing PAH (OR= 1.525, 95% CI: 1.063-2.189, P = 0.022).The positive correlation between platelet count and the risk of PAH suggests that correcting elevated platelet levels may reduce the risk of developing PAH.